Orbits of radial migrators and non-migrators around a spiral arm in N-body simulations. Issue 1 (25th January 2014) - Grand, Robert J. J.; Kawata, Daisuke; Cropper, Mark
Abstract: Recent numerical N -body simulations of spiral galaxies have shown that spiral arms in N -body simulations do not rotate rigidly as expected in classic density wave theory, but instead seem to rotate at a similar speed to the local rotation speed of the stellar disc material. This in turn yields winding, transient and recurrent spiral structure, whose corotating nature gives rise to changes in the angular momentum (radial migration) of star particles close to the spiral arm at many radii. From high-resolution N -body simulations, we highlight the evolution of strongly migrating star particles (migrators) and star particles that do not migrate (non-migrators) around a spiral arm. We investigate the individual orbit histories of migrators and non-migrators and find that there are several types of migrator and non-migrator, each with unique radial evolution. We find the important quantities that affect the orbital evolution to be the radial and tangential velocity components in combination with the azimuthal distance to the spiral arm at the time the star particle begins to feel tangential force. We contrast each type of orbit to compare how these factors combine for migrators and non-migrators. We find that the positive (negative) migrators sustain a position behind (in front of) the spiral arm, and feel continuous tangential force as long as the spiral arm persists. This is because the positive (negative) migrators are close to the apocentre (pericentre) epicycle phase during their migration, and rotate slower (faster) than the corotating spiral arm. On the other hand, non-migrators stay close to the spiral arm, and pass or are passed by the spiral arm one or two times. Although they gain or lose the angular momentum when they are behind or in front of the spiral arm, their net angular momentum change becomes close to zero. We discuss also the long-term effects of radial migration on the radial metallicity distribution and radial angular momentum and mass profiles.